Geopolitical Resonance of the VI All-Belarusian People’s Assembly - V. G. Kogut; G. N. Nuryshev (Евразийская интеграция: экономика, право, политика, 2022)
This work is aimed at studying the results of the VI All-Belarusian People’s Assembly.Aim. Determine the geopolitical dimension of the VI All-Belarusian People’s Assembly as an integration project of the Republic of Belarus.Tasks. To study the nature of preparation in the Republic of Belarus for the VI All-Belarusian People’s Assembly. Analyze the main provisions and conclusions of the report of the President of the Republic of Belarus A. G. Lukashenko and speakers at the Meeting. To generalize the geopolitical dimension of the results of the VI All-Belarusian People’s Assembly.Methodology. Study of documents of the VI All-Belarusian People’s Assembly on the basis of information and analytical technologies, including the provisions of critical geopolitics and high-quality content analysis.Results. None of the previous similar forums received such a noticeable political resonance at the preparatory stage and was not subject to oblivion after its end. Thorough preparation, the study of public opinion, the preceding broad national dialogue determined the main distinguishing feature of the Assembly. The composition of its participants quite fully reflected the social structure of the entire Belarusian society. The nature of the discussion at the Meeting was det ermined by the report of the Head of State. The overwhelming majority of delegates, showing a high level of geopolitical selfidentification, supported the main conclusions and provisions of this report. During the discussion at the Meeting, the question arose about the geopolitical security of the Republic of Belarus in a new geopolitical configuration in Europe. The assessment of Russia as the main geo-economic partner and geostrategic ally is given. The position of the delegates in relation to strengthening the efficiency of public administration and, accordingly, the geopolitical position of the Republic of Belarus has been determined.Conclusions. The geopolitical significance of Belarus today lies in the fact that it is acquiring the image of a full-fledged designer of the Eurasian space. The VI All-Belarusian Assembly became a special forum in the modern history of the republic, which took place in the fateful period of the development of Belarusian society. The VI All-Belarusian People’s Assembly became an indicator of the understanding of the Belarusian society of the geopolitical future of their country, the abili ty to “rise” to the geopolitical level of assessing the current situation, both in the republic and in the wo rld as a whole.